2019
DOI: 10.23939/chcht13.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Acrolein to Acrylic Acid Oxidation with Hydrogen Peroxide on Se-Organic Catalysts

Abstract: Catalytic performance of Se-containing organic substances, namely methylseleninic acid, benzeneseleninic acid, phenylselenol and diphenyldiselenide, has been tested as potential catalysts for unsaturated aldehydes oxidation by hydrogen peroxide. All tested substances proved to be active in the acrolein oxidation reaction but showed different efficiency regarding used solvents and the products of reaction-acrylic acid or methyl acrylate. Optimal catalyst, reaction conditions and solvent for acrylic acid synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The introduction of metal particles into the structure of hydrogels opens additional possibilities for providing them with new properties, for example, bactericidal, antifungal, fluorescent, optical, catalytic, electrical, and magnetic properties, as well as their changes in the desired direction. Such materials are already used in biotechnology and medicine [14]; in the production of packaging materials [15], microelectronics [7], optics and optoelectronics [9], chemical catalysis [16,17], and sensory devices [18]; and in other industries.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of metal particles into the structure of hydrogels opens additional possibilities for providing them with new properties, for example, bactericidal, antifungal, fluorescent, optical, catalytic, electrical, and magnetic properties, as well as their changes in the desired direction. Such materials are already used in biotechnology and medicine [14]; in the production of packaging materials [15], microelectronics [7], optics and optoelectronics [9], chemical catalysis [16,17], and sensory devices [18]; and in other industries.…”
Section: Introductionmentioning
confidence: 99%
“…1a). This phenomenon can be explained by inhibitory effect of water on the oxidation reactions as has been reported before [2]. On the other hand, previous studies of microgel colloidal properties in "water in oil" and "oil in water" systems shown that there are droplets of water formed in oil regardless the proportion of oil and water phases [3].…”
Section: Resultsmentioning
confidence: 52%
“…Two heterophase systems were used: "water in oil" (toluene:water ratio -4:1) and "oil in water" (toluene:water ratio -1:4). Catalytic performance of Se-modified microgels was compared to H 2 SeO 3 and diphenyl diselenide (DPDS) -highly active catalysts in oxidation reaction [2] and diselenide crosslinker (X-linker) that don't have surfactant properties (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature review 10,12,15,20,33,34 and our preliminary results, 32,33 the obligatory condition for the reaction to occur is the presence of a seleninic group, which, when interacting with hydrogen peroxide, gives a perseleninic group that acts as a catalyst 20 (Fig. 1b).…”
Section: Study Of the Reaction Mechanism Of Acrolein Oxidation With T...mentioning
confidence: 88%